ANALISIS INTERAKSI KOMITMEN AFEKTIF PADA LOCUS OF CONTROL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN Studi pada Karyawan PDAM Bandarmasih Kota Banjarmasin - Rena Annida; Tinik Sugiati; Rahmawati (Universitas Lambung Mangkurat, 2018)
This study aims to examine and analyze the interaction of Affective Comitment on Locus of Control on Employee Performance and the interaction of Affective Commitment on Work Environment on Employee Performance at PDAM Bandarmasih Kota Banjarmasin The result of this indicated that (i) there was no influence between Locus of Control on Employee Performance, (ii) there was an influence of Work Environment on Employee Performance, (iii) there was no interaction of Affective Commitment to the influence of Locus of Control on Employee Performance, (iv) there was an interaction of Affective Commitment to the influence of Work Environment on Employee Performance